Communication on Direct Population Administration Service Innovation (Pak Ladi) at the Pasuruan Regency Population and Civil Registration Service - Madjid, Radita Andriana; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2020)
The direct population administration service innovation (Pak Ladi) is an innovation from the Pasuruan Regency Dispendukcapil. This study aims to analyze communication in population administration service innovation. In addition, this study aims to determine the obstacles that occur in communication in direct population administration services (Pak Ladi) in Pasuruan Regency. This research uses structural innovation theory. The method used in this study is a qualitative descriptive method with the technique of determining the informants taken by the author in this study, namely the service implementers (Department of Population and Civil Registration) Pasuruan Regency and the community as recipients of population administration services. The results of this study indicate that Communication on Direct Population Administration Services (Pak Ladi) in Pasuruan Regency is still not optimal. This is due to obstacles such as the lack of socialization from the government to the community and the lack of coordination between agencies. Based on the results of data analysis techniques, namely data collection (data collection), data reduction (data reduction), data presentation (data display), and drawing conclusions or verification (conclutions).